2017
DOI: 10.1016/j.cels.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Enzyme Kinetics Reveal Specificity Principles for RNA-Guided Nucleases in RNA Interference and CRISPR-Based Genome Editing

Abstract: SUMMARY RNA-guided nucleases (RGNs) provide sequence-specific gene regulation through base-pairing interactions between a small RNA guide and target RNA or DNA. RGN systems, which include CRISPR-Cas9 and RNA interference (RNAi), hold tremendous promise as programmable tools for engineering and therapeutic purposes. However, pervasive targeting of sequences that closely resemble the intended target has remained a major challenge, limiting the reliability and interpretation of RGN activity and the range of possi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 76 publications
6
74
0
Order By: Relevance
“…These results indicate that target site unfolding is the rate-limiting step that determines miRISC activity in vivo. Furthermore, this structure-limiting scenario reveals that the ribonuclease AGO undergoes "sticky regime" activation (51), where substrate mRNAs associate and dissociate with AGO more slowly than they are being cleaved.…”
Section: The Unfolding Of the Target Site Structure Is The Primary Dementioning
confidence: 99%
“…These results indicate that target site unfolding is the rate-limiting step that determines miRISC activity in vivo. Furthermore, this structure-limiting scenario reveals that the ribonuclease AGO undergoes "sticky regime" activation (51), where substrate mRNAs associate and dissociate with AGO more slowly than they are being cleaved.…”
Section: The Unfolding Of the Target Site Structure Is The Primary Dementioning
confidence: 99%
“…Biochemically, we found that these Cas9 variants cleaved the on-target DNA with rates similar to that of wild-type (WT) SpCas9, whereas their cleavage activity was significantly reduced on substrates bearing mismatches (Extended Data Figures 1a, 2a). To test the hypothesis that SpCas9 with its single-guide RNA (sgRNA) might exhibit a greater affinity for its target than is required for effective recognition 9,11 , we measured DNA binding affinity and cleavage of SpCas9-HF1 and eSpCas9(1.1) variants. Contrary to a potential hypothesis that mutating these charged residues to alanine weakens target binding 11 , the affinities of these variants for on-target and PAM-distal mismatched substrates were similar to WT SpCas9 (Figure 1b, Extended Data Figures 1a, 2b), indicating that cleavage specificity is improved through a mechanism distinct from a reduction of target binding affinity 11 .…”
mentioning
confidence: 99%
“…It was argued that this might be the way for bacteria to fight quickly mutating viruses, in which the original target sequence would slightly change (17,28). The probability of such off-target cutting events can reach up to 10−20%, and this significantly complicates the application of CRISPR systems for genetic applications (11).…”
Section: Dynamics Of Search With Off-target Cuttingmentioning
confidence: 99%
“…Despite the tremendous importance of CRISPR-associated processes, there is a surprisingly small number of theoretical investigations concerned with molecular mechanisms and dynamics of underlying processes in these systems (13,27,28). A recent computational study probed structural dynamics of the CRISPR-Cas9 RNA guided DNA cleavage by utilizing various high-resolution structures of Cas9 proteins in different states (13).…”
Section: Introductionmentioning
confidence: 99%